Design History of the www: Website Development from the Perspective of Genre and Style Theory - Ida Engholm (Artifact, 2007)
Abstract Since the emergence of the World Wide Web in the early 1990s, the internet has become one of the most important tools for information, entertainment, trade, and social contacts. From a primitive, text-based medium, the web has become a highly advanced and complex mass-multi-medium representing multiple forms of design. Despite the web’s importance as a design medium, the development of website design has only been sporadically described. As yet, we have no historical, chronological descriptions of web design history similar to what we find, for example, in the study of art or “analogue” design history. The article demonstrates how website development can be analysed from a genealogical point of view. It does so by pointing out a number of genre and style formations and discussing their ideological and cultural sources. It is argued that the main engine for web development is the demand for renewal and differentiation from producers and users, which leads to various technical, functional, and symbolic distinction strategies for website design.